Reproductive features of the Antarctic silverfish (Pleuragramma antarctica) from the western Ross Sea - Laura Ghigliotti; Sara Ferrando; Erica Carlig; Davide Di Blasi; Lorenzo Gallus; Eva Pisano; Stuart Hanchet; Marino Vacchi (Polar Biology, 2017)

Response to the opinion paper by Ainley et al. - Stuart Hanchet; Alistair Dunn; Steven Parker; Peter Horn; Darren Stevens; Sophie Mormede (Hydrobiologia, 2016)

Erratum to: The Antarctic toothfish (Dissostichus mawsoni): biology, ecology, and life history in the Ross Sea region - Stuart Hanchet; Alistair Dunn; Steven Parker; Peter Horn; Darren Stevens; Sophie Mormede (Hydrobiologia, 2015)

The Antarctic toothfish (Dissostichus mawsoni): biology, ecology, and life history in the Ross Sea region - Stuart Hanchet; Alistair Dunn; Steven Parker; Peter Horn; Darren Stevens; Sophie Mormede (Hydrobiologia, 2015)

Skip spawning as a reproductive strategy in Antarctic fish species: the Antarctic silverfish (Pleuragramma antarctica) case study - Ghigliotti Laura; Ferrando Sara; Carlig Erica; Di Blasi Davide; Gallus Lorenzo; Pisano Eva; Hanchet Stuart; Vacchi Marino (Frontiers in Marine Science, 2015)

Fish species of New Zealand. A photographic guide. By JorgeHirt‐Chabbert. Published in 2006 by Reed Publishing (NZ) Ltd, 39 Rawene Rd, Birkenhead, Auckland 10, New Zealand (www.reed.co.nz). 136 p., softcover. ISBN‐10: 0–7900–1040–2. Price NZ$39.99. - Stuart Hanchet (New Zealand Journal of Marine and Freshwater Research, 2008)

Stock structure of southern blue whiting ( Micromesistius australis) in New Zealand waters - Stuart Hanchet (New Zealand Journal of Marine and Freshwater Research, 1999)
Data on the reproduction, growth, and morphometric characteristics of southern blue whiting (Micromesistius australis Norman) were examined to determine its stock structure in New Zealand waters. Consistent differences in the size distribution of fish, and in the timing of spawning were found between spawning grounds on the Bounty Platform, Pukaki Rise, Auckland Islands Shelf, and Campbell Island Rise. Significant differences in morphometric characteristics were found between fish from the Bounty Platform, Pukaki Rise, and Campbell Island Rise and significant differences in growth rates were found between the Bounty Platform and Campbell Island Rise. The results provide strong evidence that fish return to spawn on the grounds to which they first recruit, and suggest that the four areas should be assessed and managed as separate stocks.

Albatross predation of juvenile southern blue whiting ( Micromesistius australis ) on the Campbell Plateau - Yves Cherel; Sue Waugh; Stuart Hanchet (New Zealand Journal of Marine and Freshwater Research, 1999)
Dietary samples collected at Campbell Island in summer 1997 indicate that southern blue whiting ( Micromesistius australis ) formed the bulk of the food of black‐browed albatrosses ( Diomedea melanophrys impavida ) during the chick‐rearing period. Birds preyed upon a single size class of fish with a mode at 80–90 mm standard length; fish were 4–5 months old and belonged to the + age group. Satellite tracking showed that, when performing trips of short duration, adult albatrosses foraged within the 1000 m depth contour in the subantarctic zone north of Campbell Island. The feeding ecology of albatrosses thus suggests that juvenile (+) southern blue whiting are pelagic and occur in dense schools in the top 5 m of the water column over the Campbell Plateau during the summer months. The high reliance of birds on juvenile southern blue whiting during the chick‐rearing period has implications for the management of the southern blue whiting fishery and the conservation of black‐browed albatrosses and other marine predators occurring in the New Zealand subantarctic area.